Gut Glucosinolate Metabolism and Isothiocyanate Production. Issue 18 (5th July 2018) - Narbad, Arjan; Rossiter, John Trevor
Abstract: The glucosinolate‐myrosinase system in plants has been well studied over the years while relatively little research has been undertaken on the bacterial metabolism of glucosinolates. The products of myrosinase‐based glucosinolate hydrolysis in the human gut are important to health, particularly the isothiocyanates, as they are shown to have anticancer properties as well as other beneficial roles in human health. This review is concerned with the bacterial metabolism of glucosinolates but is not restricted to the human gut. Isothiocyanate production and nitrile formation are discussed together with the mechanisms of the formation of these compounds. Side chain modification of the methylsulfinylalkyl glucosinolates is reviewed and the implications for bioactivity of the resultant products are also discussed. Abstract : Gut bacteria play an important role in the hydrolysis of dietary glucosinolates to the isothiocyanates that are known to have chemoprotective functions. The bacterial enzymes involved have yet to be fully characterized. In the gastrointestinal tract, this hydrolytic process appears complex and a number of bacterial metabolic pathways are proposed that result in the production of isothiocyanates or nitrile products.